Uncertainty and Information Acquisition: Evidence from Firms and Households - Heiner Mikosch; Christopher Roth; Samad Sarferaz; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
We leverage the small open economy Switzerland as a testing ground for basic premises of macroeconomic models of endogenous information acquisition, using tailored surveys of firms and households. First, we show that firms perceive a greater exposure to exchange rate movements than households, which is reflected in higher levels of information acquisition and less dispersed beliefs about past and future exchange rate realizations. Similarly, within the two samples, acquisition of exchange rate information strongly increases in various proxies for stake size. Second, households who perceive higher costs of acquiring or processing information acquire less information. Finally, an exogenous increase in the perceived uncertainty of the exchange rate increases firms' demand for a report about exchange rate developments, but not households'. Our findings inform the modeling of information frictions in macroeconomics.
Keywords: D12; D14; D83; D84; E32; G11; 330; Information acquisition; Uncertainty; Stake Size; Firms; Households